On the Third Moduli of Continuity - Bezkryla, S. I.; Nesterenko, A. N.; Chaikovs'kyi, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
An inequality for the third uniform moduli of continuity is proved. This inequality implies that an arbitrary 3-majorant is not necessarily a modulus of continuity of order 3.